THE BALANCE BOARD GAME DEVELOPS DYNAMIC BALANCE MORE THAN BALANCE BEAM GAMES FOR CHILDREN AGE 5 – 6 IN PRANDNYANDARI 1 KINDERGARDEN KEROBOKAN - Wulandari, Ayu; Wibawa, Ari; Primayanti, I Dewa Ayu Inten Dwi (Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT The aim of this research is to compare balance board game and balance beam game in developing dynamic balance of children age 5 to 6 in Pradnyandari 1 Kindergarden Kerobokan. This research is experimental research in which it used randomized pretest-postest control group design with 32 children which divided into two groups. Group 1 was given balance board game and group 2 was given balance beam game. The difference of the average before and after practice of group one was tested by using Wilcoxon Match Pair Test with result p = 0.000 (p<0.05) and group two was tested using Wilcoxon Match Pair Test with result p = 0.000 (p<0.05). At difference test between group one and group two using Mann-Whitney U-test shows significant difference with result p = 0.000 (p<0.05). The conclusion of this research is balance board game develops dynamic balance, balance beam game develops dynamic balance and balance board game more develop dynamic balance than balance beam game. Keyword: Dynamic Balance, Balance Board, Balance Beam, Modified Bass Test.